2016
DOI: 10.1136/bmjopen-2015-010973
|View full text |Cite
|
Sign up to set email alerts
|

Trends of CT utilisation in an emergency department in Taiwan: a 5-year retrospective study

Abstract: ObjectivesTo investigate the association between the trends of CT utilisation in an emergency department (ED) and changes in clinical imaging practice and patients' disposition.SettingA hospital-based retrospective observational study of a public 1520-bed referral medical centre in Taiwan.ParticipantsAdult ED visits (aged ≥18 years) during 2009–2013, with or without receiving CT, were enrolled as the study participants.Main outcome measuresFor all enrolled ED visits, we retrospectively analysed: (1) demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 27 publications
(21 reference statements)
0
35
0
Order By: Relevance
“…Recent studies suggest that if appropriate clinical criteria are followed, 20–40% of CT scans could be avoided (2022). Similar to Japan, CT use has been increasing in other Asian countries too (23, 24). Hu et al (24) reported that CT utilization rates increased significantly between 2009 and 2013 in emergency departments.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies suggest that if appropriate clinical criteria are followed, 20–40% of CT scans could be avoided (2022). Similar to Japan, CT use has been increasing in other Asian countries too (23, 24). Hu et al (24) reported that CT utilization rates increased significantly between 2009 and 2013 in emergency departments.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to Japan, CT use has been increasing in other Asian countries too (23, 24). Hu et al (24) reported that CT utilization rates increased significantly between 2009 and 2013 in emergency departments. They speculated that CT scans may be used for rapid screening to facilitate patients' disposition rather than to confirm diagnosis, given the stress of emergency department crowding and potential lawsuits.…”
Section: Discussionmentioning
confidence: 98%
“…For urinary tract infections, the figure went up from 0 in 1996 to 48% of presentations in 2016 (13). A Taiwanese study found that although the use of CT had increased in emergency departments, the hospital admission of patients who underwent scans had decreased (14), indicating that the use of CT has largely been for non-emergency conditions and to “rule-out” a particular diagnosis.…”
Section: Ct Use Has Increased Rapidlymentioning
confidence: 99%
“…Chen et al stated that the annual CT examination frequency per 1000 population increased by an average of 8.1% per year from 1997 to 2008 [3]. Hu et al found that the annual frequency of CT scans increased from 11.1% in 2009 to 17.7% in 2013, and that the frequency increased for all age groups in Taiwan [4]. The number of CT examinations increased rapidly, with an average annual growth rate of 7.6%, and this trend was similar to those in other countries [5].…”
Section: Introductionmentioning
confidence: 99%